Design and Construction of IoT-Based Overvoltage and Undervoltage Detection Devices - Mahendra, Luki Septya; Putra, Putu Agus Mahadi; Kurniawan, Agus Dinantya Dwi; Suharyanto, Hendik Eko Hadi; Raharja, Lucky Pradigta Setiya; Arif, Yahya Chusna (Journal of Electrical Engineering and Computer (JEECOM), 2025)
In this research, designed an overvoltage and undervoltage fault detector based on the Internet of Things (IoT), which aims to monitor the quality of electrical voltage in detecting overvoltage / undervoltage faults that change instantly with real-time monitoring. This system detects voltage disturbances using the PZEM-004t sensor by considering PLN standards. The overvoltage is above +5% normal voltage and for undervoltage below -10% normal voltage. Voltage disturbances are injected through the transformer configuration to generate overvoltage / undervoltage instantly. Furthermore, the voltage that has been read by the sensor is sent to the Blynk platform as a monitoring system. The transformer configuration is simulated first, with an overvoltage result is 251.8 V and an undervoltage is 110.6 V. In the results of the hardware transformer configuration test, the overvoltage injection is 253 V and the undervoltage is 117.3 V. The data displayed by the monitoring system is compared with the Fluke 43B measuring instrument to be calibrated, with an average error of 1.2%. Monitoring data can be accessed via gadgets. So that preventive actions and analysis can be carried out to reduce the risk of losses due to voltage disturbances.